Estudos e propriedades de adsorção de Pb(II), Cr(III) e Hg(II) sobre a superfície de sílica gel e com as sílicas quimicamente modificadas em solução aquosa - Moraes, Daniela Aparecida Gerardi (2005)
In this work we investigated the adsorption at silica gel, SF-3-APTS and SF-3- C1PTS surfaces of Cr(III), Pb(II) and Hg(II) complex anions ffom aqueous solution, in the presence and absence o f several electrolytes. It was observed the absorption of Cr(III) occurs continually in the case of silica gel and SF-3-C1PTS supports, but not with SF-3-APTS. The presence of HC1, KC1 and LiCl in the electrolyte increases the adsorption of Cr(III) on silica gel, probably due the excess of Cl", which favours [ Cr(Cl6)]3" complex formation. The adsorption of Cr(III) on SF-3-APTS appears to involve the same complex ion, but due the relatively small size of Li+, is more effective in the presence o f LiCl. On the other hand a decrease of absorption of Cr(III) on SF-3-C1PTS was observed in the presence of LiCl, attributed to ionic pair formation such as LimCrClnz"n+m where m(< | z-n | ). Pb(II) also adsorbs on silica gel and SF-3-C1PTS continuously, but more on silica gel attributed which is to the presence of free silianes. On SF-3-APTS this ion adsorbs only at high Pb(II) concentrations. In presence o f HC1, KCI and LiCl adsorption increases due the formation o f complexes such as PbCl„z'n. Hg(II) adsorption takes place at the three supports, but more efíiciently at silica gel again due to the presence of free silanes, however, in the presence of the three electrolytes its adsorption decreases. In the case of SF-3-C1PTS the decrease in adsorption is attributed to formation of ionic pairs such as YmMClnz"n+m, where Y (H+, K+ or Li+) m (< | z-n | ). On SF-3-APTS no electrolyte influence was detected for these cations